Pelatihan Pembuatan Dodol “UBALU” (Ubi Jalar Ungu) - Baharuddin, Riski Aprilianti; Hasanah, Dillah Faradilla; Fiddah, Andi Izatul; Arisah, Nur (Universitas Muhammadiyah Sidenreng Rappang, 2024)
In Indonesia, sweet potatoes are generally a side food ingredient. Meanwhile in Irian Jaya, sweet potatoes are used as a staple food. One of the areas producing purple sweet potatoes is the people of Gowa, especially the Tahfidzul Qur'an Pondok Tahfidzul Qur'an, Gowa As-Syarif Education Foundation. Where the average community commodity is planting purple sweet potatoes. However, unfortunately, after harvesting, people only immediately sell the purple sweet potatoes to collectors, or usually sell them to people who are visiting the place as souvenirs or souvenirs from the cottage, so their economic value is still low. Therefore, in order to overcome this problem, the aim of the community service carried out by the community service is to innovate purple sweet potatoes into dodol so that they are suitable for sale to local communities, throughout Indonesia and abroad, and purple sweet potatoes have high economic value. The Community Partnership Program Team was moved to provide training in the skills of making dodol made from purple sweet potato as the basic ingredient, which was given the name Dodol